Estrogenized HSA induced high-affinity autoantibodies in breast cancer - Novel biomarker for early detection - Sherwani, Subuhi; Khan, Mohd Wajid Ali; Khan, Wahid Ali; Rajendrasozhan, Saravanan; Al-Motair, Khalid; Khan, Hamda; Ahmad, Saheem (Frontiers in Oncology, 2024)
ObjectiveBreast cancer (BC) is the second most prevalent cancer worldwide. Estrogen has been increasingly recognized as a major contributor to the development of BC, playing a more critical role than previously understood. Estrogen derived nucleic acid and protein adducts have been shown to play significant roles in BC development and progression. However, the alterations in molecular mechanism(s) and immune pathways arising as a result of estrogenization still remain elusive.Patients and methods4-hydroxyestradiol (4-OHE2) was used for adduct formation with protein human serum albumin (HSA) (4-OHE2-HSA). The affinity of antibodies for 4-OHE2-HSA was evaluated in breast cancer patients. Immunoassays (direct binding ELISA, inhibition ELISA, and quantitative precipitin titration assay) were used to assess autoantibodies against estrogenized HSA in BC patients (n = 85) and healthy controls (n = 45).ResultsEstrogenization of HSA altered both its structure and function and compromised its interactions with various HSA-binding proteins. BC patients demonstrated high-affinity antibodies against 4-OHE2-HSA as compared to HSA (p < 0.05). Additionally, cytokines Interleukin (IL)-1, IL-6 and tumor necrosis factor-alpha (TNF-α) were significantly elevated in BC patients as compared to the control group. Several factors, such as chemotherapy, estrogen receptors (ERs), and combination of surgery and chemotherapy, influenced the production of antibodies in cancer patients. The affinity constant for estrogenized HSA was 1.31 × 10-7 M, while for HSA and 4-OHE2, it was 1.68 × 10-6 M and 1.36 × 10-6 M, respectively.ConclusionsEstrogenized HSA is highly immunogenic, resulting in functional alterations. High affinity antibodies were detected in BC patients against 4-OHE2-HSA. Consequently, 4-OHE2-HSA may serve as a novel molecular target for potential cancer therapeutics. Furthermore, autoantibodies against 4-OHE2-HSA could serve as a potential biomarker for early detection of BC.